Formation and yield of multi-walled carbon nanotubes synthesized via chemical vapour deposition routes using different metal-based catalysts of FeCoNiAl, CoNiAl and FeNiAl-LDH - Hussein, Mohd Zobir; Mohamad Jaafar, Adila; Yahaya, Asmah; Masarudin, Mas Jaffri; Zainal, Zulkarnain (Multidisciplinary Digital Publishing Institute, 2014)
Multi-walled carbon nanotubes (MWCNTs) were prepared via chemical vapor deposition (CVD) using a series of different catalysts, derived from FeCoNiAl, CoNiAl and FeNiAl layered double hydroxides (LDHs). Catalyst-active particles were obtained by calcination of LDHs at 800°C for 5 h. Nitrogen and hexane were used as the carrier gas and carbon source respectively, for preparation of MWCNTs using CVD methods at 800°C. MWCNTs were allowed to grow for 30 min on the catalyst spread on an alumina boat in a quartz tube. The materials were subsequently characterized through X-ray diffraction, Fourier transform infrared spectroscopy, surface area analysis, field emission scanning electron microscopy and transmission electron microscopy. It was determined that size and yield of MWCNTs varied depending on the type of LDH catalyst precursor that is used during synthesis. MWCNTs obtained using CoNiAl-LDH as the catalyst precursor showed smaller diameter and higher yield compared to FeCoNiAl and FeNiAl LDHs.